Improving Heat-Exchange Network Efficiency Through Front-End Process Modification in the Drying Oil Production from Acetylated Castor Oil - Soebiakto, Devieazy Poetri; Sabrina, Ilma; Alfinurazizah, Alfinurazizah; Ahmad, Aisha; Chrisnantoe, Valenciana; Ramadhani, Hawwa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Enhancing the energy efficiency of drying oil production is critical for reducing utility consumption and advancing process sustainability. This study explores front end heat integration modifications by replacing the fired heater with a process to process heat exchanger and employing the high-temperature bottom stream of the distillation column as an internal heat source. Comparative simulations using Aspen HYSYS V11 were performed for both the baseline and modified flowsheets. The redesigned system enables internal preheating through mixing and heat recovery, thereby eliminating the fired heater and lowering the cooling demand in downstream units. Consequently, the total net energy requirement decreases from 8.895×10⁶ kJ/h to 7.363×10⁶ kJ/h, corresponding to an efficiency gain of approximately 17.2%, while maintaining product purity at 99.97%. These results highlight the effectiveness of early stage heat integration strategies in reducing external utility demand, improving energy efficiency, and supporting more sustainable drying oil production. Future research may extend to comprehensive heat exchanger network (HEN) optimization and renewable-assisted heat recovery schemes. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).